PENGEMBANGAN MODEL-MODEL PENDUGA INDEKS TEMPAT TUMBUH DAN PERTUMBUHAN TEGAKAN JABON (Neolamarckia cadamba (Roxb.)) DI HUTAN RAKYAT (Site Index and Growth of Neolamarckia cadamba (Roxb.) Stands in Community Forest) - Lutfy Abdulah; Nina Mindawati; Mira Yulianti (Jurnal Penelitian Hutan Tanaman, 2020)
ABSTRACTThe existence of community forests is one of the efforts to provide wood raw materials by the community. This effort has limitations such as non-standardized silvicultural techniques and cutting cycle, and no annual growth measurements. This is a problem in compiling tables of community forest stands. Therefore, no adequate information on the stands’ growth to support the promotion of community forest development. This study was conducted to overcome those problems using modeling techniques involving several different measurement locations and plant ages. The parameters of the built model were the elevation model, the quality of the place to grow, and the tree diameter of each class of quality of jabon stands’ site. The research objective was to create a growth and site quality model and provide data on jabon diameter growth in each class. The results showed that the Schumacher model could be used in estimating the tree height of jabon, while the ChapmanRichards model was excellent in classifying the quality of growing sites of jabon. The only valid model for diameter growth of jabon stands was Bonita II.                                               ABSTRAKKeberadaan hutan rakyat merupakan salah satu upaya penyediaan bahan baku kayu oleh  masyarakat. Upaya ini memiliki batasan seperti teknik silvikultur dan umur tebang yang  tidak baku, serta pengukuran pertumbuhan yang tidak dilakukan setiap tahun. Hal ini menjadi masalah dalam menyusun tabel tegakan hutan rakyat. Dampaknya adalah informasi pertumbuhan tegakan tidak ada sehingga promosi pembangunan hutan rakyat menjadi terbatas. Untuk mengatasi masalah tersebut, dilakukan penelitian dengan menggunakan teknik pemodelan yang melibatkan beberapa lokasi pengukuran dan umur tanaman jabon yang berbeda. Parameter model yang dibangun adalah model peninggi, kualitas tempat tumbuh dan diameter pohon setiap kelas kualitas tempat tumbuh. Tujuan penelitian adalah membuat model peninggi dan kualitas tempat tumbuh serta menyediakan data pertumbuhan diameter pohon di setiap kelas. Hasil penelitian meunjukkan bahwa model Schumacher dapat digunakan dalam menduga tinggi pohon jabon, sedangkan model Chapman-Richards sangat baik dalam mengklasifikasi kualitas tempat tumbuh jabon. Model pertumbuhan diameter tegakan jabon yang valid hanya pada Bonita II.